Getting Better or Worse? General Health Status of 9th Grade Students in Orhangazi, Bursa, Turkey. (2008) - Alper, Zuleyha; Ozdemir, Hakan; Uncu, Yesim; Ozcakir, Alis; Sadikoglu, Ganime; Bayram, Nuran
Abstract : Adolescence is a transition phase from childhood to adulthood. In this period, rapid changes and development in their physical, biological, psychological, and social lives take place. While adolescents have to acquire many qualifications, they are faced with many problems, especially those that risk their health. In Turkey, one of the most important issues contributing to risky behaviors is the 1 st Phase Nationwide High School Exam. Students must pass this phase in order to be in good high schools and to then pass the 2 nd Phase University Exam. Most of their time is spent studying in school or in private teaching institutions, and less time is spent with their families or participating in social activities. In order to examine the effects on 9 th grade students after the 1 st Phase exams, we conducted this study with 1192 students in Bursa, Orhangazi. Data to evaluate students by socioeconomic status, body mass index (BMI), dietary, smoking, and physical activity behaviors and psychological status were collected via classroom questionnaires. We aimed to determine and evaluate the general characteristics and physical examination findings, to some extent, in a nationally representative sample of 9 th grade students a year following the Nationwide High School Exam.